Pengaruh Manajemen Pakan Dan Lingkungan Terhadap Efisiensi Reproduksi Domba Lokal - Nurhabibah; Amalia (Jurnal Ilmu Peternakan Indonesia, 2025)
The efficiency of sheep reproduction is influenced by various factors, including feed management and environmental conditions. This study aims to evaluate the effect of feed management and environmental conditions on the reproductive efficiency of local sheep in Jambi. A total of 60 local sheep were divided into three treatment groups: (A) high-quality feed with an optimal environment, (B) standard feed with an optimal environment, and (C) standard feed with a suboptimal environment. The reproductive parameters observed included estrus rate, conception rate, pregnancy rate, and litter size. The results showed that Group A had the highest reproductive efficiency, with an estrus rate of 95%, a conception rate of 85%, and an average litter size of 1.8 lambs per ewe. In contrast, Group C had the lowest reproductive efficiency, with a 65% estrus rate, a 50% conception rate, and an average litter size of 1.2 lambs per ewe. The findings indicate that nutritional intake and environmental factors significantly affect reproductive efficiency, with high-quality feed and optimal environmental conditions yielding the best reproductive performance. This study suggests that improving feed management and optimizing environmental conditions can enhance sheep productivity and contribute to the sustainability of local sheep farming.